2012
DOI: 10.1007/s00041-012-9223-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Gagliardo-Nirenberg type inequality in the critical Sobolev-Morrey space

Abstract: Our main purpose in this article is to establish a Gagliardo-Nirenberg type inequality in the critical Sobolev-Morrey space H M the growth order r 1− 1 p as r → ∞. The inequality (GN) implies that the growth order as r → ∞ is linear, which might look worse compared to the case of the critical Sobolev space. Communicated by Hans Triebel. Y. Sawano ( ) J Fourier Anal ApplHowever, we investigate the optimality of the growth order and prove that this linear order is best-possible. Furthermore, as several applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…In [54], it was shown that this function space E 0 pq2 (R n ) is equivalent to the Hardy-Morrey space defined by Jia and Wang in [22]. See [1,20,22,63] for more about Hardy Morrey spaces. In [32,Theorem 4.2], Mazzucato proved that the Triebel-Lizorkin space E 0 pq2 (R n ) with 1 < q ≤ p < ∞ is equivalent to the Morrey space M p q (R n ).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In [54], it was shown that this function space E 0 pq2 (R n ) is equivalent to the Hardy-Morrey space defined by Jia and Wang in [22]. See [1,20,22,63] for more about Hardy Morrey spaces. In [32,Theorem 4.2], Mazzucato proved that the Triebel-Lizorkin space E 0 pq2 (R n ) with 1 < q ≤ p < ∞ is equivalent to the Morrey space M p q (R n ).…”
Section: 2mentioning
confidence: 99%
“…(1) Let r = 1 in Proposition 7.3. The authors in [63] showed that (3) One can not replace min(1, r) by 1 in (7.10) when r ∈ (0, 1). Assume to the contrary that this is possible.…”
Section: 2mentioning
confidence: 99%
“…Take a function ϕ belonging to the schwartz class S(boldRn), which is non‐degenerate in the sense that Rnϕ(x)dx0.Then for the tempered distribution fscriptS, define fHscriptMqp:=‖‖trueprefixsupjZ|ϕj*f|Mqp,where ϕj:=2jnϕ(2j·) for jZ. We define the norm of the Sobolev–Morrey space HscriptMp,qs for sR, 0<qp< by using the Hardy–Morrey space as follows: fHscriptMp,qs:=‖‖(1Δ)s2fHscriptMqp.In , Sawano and Wadade obtained the following result: Proposition [32, Theorem 5.1] Let 1<q<p< and φ(t)=(1+tn)1p()loge+1tn...…”
Section: Introductionmentioning
confidence: 99%
“…We refer to [36] for a counterexample showing that (1.5) is no longer true for α = d p . Meanwhile, the function q(·) can be used to describe the Hardy-Littlewood maximal operator control in very subtle settings.…”
Section: ( ) P(·)q(·) (X ·) Is Convex On [0 ∞) For Every X ∈ Xmentioning
confidence: 99%